ORME Dl TETRAPODI NELLA FORMAZIONE Dl WERFEN DEL RECOARESE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A slab with the tetrapod footprints Rhynchosauroides cf. schochardti (R. von Lilienstern, 1939) is described from the Werfen Fm. of Recoaro area (Vicentinian Alps). The slab is coming from red siltitic facies of the "Monte Naro Breccias" (Upper Scythian — Lower Anisian ? sedimentary cicles).
Keywords: Tetrapod footprints; Scythian; Venetian Alps (Italy).